2009
DOI: 10.1007/s11284-009-0649-7
|View full text |Cite
|
Sign up to set email alerts
|

Corridors, local food resources, and climatic conditions affect the utilization of the urban environment by the Black‐headed Gull Larus ridibundus in winter

Abstract: Black-headed Gulls Larus ridibundus (BHGs) in urban areas are a public nuisance. The aim of this study is to investigate the factors affecting the occurrence and abundance of the BHG foraging in urban areas in winter. The study was conducted in the city of Krakow (southern Poland) in four easily identifiable urban habitats: (1) areas with blocks of flats, (2) areas with congested housing, (3) detached single-family housing and (4) green areas. In each of these four habitats, 60 small (1-ha) plots were randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 37 publications
1
23
1
1
Order By: Relevance
“…This increasing preference for anthropogenic food that Black-headed Gulls display as urbanicity increases, compares positively with previous studies of gulls (Raven & Coulson 1997, Auman et al 2008, Maciusik et al 2010, though ours is the first study to attempt to discern what the factors underlying this preference may be. Our results also demonstrated a difference in behavioural response to artificially provisioned foods along the urban-rural gradient suggesting that Blackheaded Gulls wintering along the Sefton Coast do not commonly move between habitats during the winter.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This increasing preference for anthropogenic food that Black-headed Gulls display as urbanicity increases, compares positively with previous studies of gulls (Raven & Coulson 1997, Auman et al 2008, Maciusik et al 2010, though ours is the first study to attempt to discern what the factors underlying this preference may be. Our results also demonstrated a difference in behavioural response to artificially provisioned foods along the urban-rural gradient suggesting that Blackheaded Gulls wintering along the Sefton Coast do not commonly move between habitats during the winter.…”
Section: Discussionsupporting
confidence: 84%
“…Gulls are a good example of this, and much research has been conducted suggesting that urban gulls are reliant on these food sources (Ewins et al 1994, Brousseau et al 1996, Belant et al 1998, Duhem et al 2003a, Duhem et al 2005, Kim & Monaghan 2006, Auman et al 2008. For example, Maciusik et al (2010) found that the abundance of the Black-headed Gull Chroicocephalus ridibundus, Linnaeus, 1766) in areas of Krakow, Poland, was positively correlated with the number of litter bins in that area. Despite anthropogenic food being found to be detrimental to many bird species (Belant et al 1998, Annett & Pierotti 1999, Boal & Mannan 1999, research has shown that anthropogenic food refuse can be beneficial to gulls in terms of their size and condition (Auman et al 2008) and reproductive success (Blount et al 2002, Duhem et al 2005.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…Secondly, people often visit such places and frequently feed birds, especially in city parks. Elements of the original, pre-urban landscape, such as remnant forests or trees and open fields, together with lawns, weedy vegetation, and lower building density positively correlate to the abundance of many birds in towns (Chace & Walsh 2006, Maciusik et al 2010.…”
Section: Discussionmentioning
confidence: 99%
“…We distinguished between local roads and regional/national roads because the former are characterized by little traffic (usually much fewer than 100 vehicles per hour), whereas the latter represent roads with [500 vehicles per hour (authors' unpublished observations). Variables 14-15 may be indicators of the site's safety from predators, variables 16-17 describe the proximity of roosting areas or migration/dispersal corridors, as has been demonstrated for other waterbirds (Skórka et al 2009;Maciusik et al 2010). The lake size of 10 ha was chosen because it was the smallest lake where roosting geese were observed in the area (authors' unpublished observations).…”
Section: Bird Surveysmentioning
confidence: 99%